A novel fractional delayed matrix cosine and sine - Mahmudov, N., I (Pergamon-Elsevier Science Ltd, 2019)
We introduce the fractional delayed matrix cosine and sine functions and use the variation of constants method to obtain an explicit formula for a solution to the initial value problem for a Riemann-Liouville sequential fractional linear time-delay system of order 1 < 2 alpha <= 2. Our results extend those for fractional linear time-delay systems and novel for the classical case alpha = 1. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fractional linear delay systems; Delayed matrix cosine; Delayed matrix sine